2013
DOI: 10.7205/milmed-d-12-00399
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Military Dental Capabilities in Mass Fatality Situations

Abstract: Recent experience with the New Zealand Defence Force in supporting the national disaster victim identification operation following destructive earthquakes in Canterbury, New Zealand, highlights the important role military forensic odontology capabilities can provide in supporting a national disaster response. Military dental personnel are well-trained, practiced, and prepared to support short-notice contingencies and can provide important immediate response augmentation to Disaster Victim Identification teams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…This suggests an additional mechanism by which SOCS6 regulates insulin signaling downstream of the receptor to control glucose metabolism. Similar to the engagement of LRIG1 with many RTKs, in vitro studies suggest that SOCS proteins regulate multiple RTKs including c-KIT, FLT3, IR, IGF-1R, and EGFR by enhancing their degradation via recruitment of E3 ubiquitin ligase complexes (Banks et al, 2005;Kario et al, 2005;Krebs et al, 2002;Nicholson et al, 2005;Trengrove and Gray, 2013). A subset of SOCS proteins -SOCS2, SOCS6, and SOCS7protect RTKs from SOCS-mediated degradation by interacting with the domains of other SOCS proteins responsible for the recruitment of E3 ubiquitin ligase complexes (Piessevaux et al, 2006).…”
Section: Late Attenuation Of Rtk Signaling Via Receptor Ubiquitination and Degradationmentioning
confidence: 97%
See 1 more Smart Citation
“…This suggests an additional mechanism by which SOCS6 regulates insulin signaling downstream of the receptor to control glucose metabolism. Similar to the engagement of LRIG1 with many RTKs, in vitro studies suggest that SOCS proteins regulate multiple RTKs including c-KIT, FLT3, IR, IGF-1R, and EGFR by enhancing their degradation via recruitment of E3 ubiquitin ligase complexes (Banks et al, 2005;Kario et al, 2005;Krebs et al, 2002;Nicholson et al, 2005;Trengrove and Gray, 2013). A subset of SOCS proteins -SOCS2, SOCS6, and SOCS7protect RTKs from SOCS-mediated degradation by interacting with the domains of other SOCS proteins responsible for the recruitment of E3 ubiquitin ligase complexes (Piessevaux et al, 2006).…”
Section: Late Attenuation Of Rtk Signaling Via Receptor Ubiquitination and Degradationmentioning
confidence: 97%
“…Although the biological roles of SOCS proteins have traditionally been considered in the context of cytokine receptor signaling through the JAK/STAT pathway in immunity and hematopoiesis, emerging evidence implicates SOCS proteins in the control of RTK signaling during development (Supplemental Table 1) (Trengrove and Gray, 2013). In vitro and in vivo studies demonstrated that SOCS2 exerts a dual role in the regulation of EGF signaling: Socs2 knockout mice displayed increased intestinal growth due to enhanced responsiveness to EGF (Michaylira et al, 2006), and cortical neurons derived from transgenic Socs2 overexpressing mice had increased neural outgrowth, apparently also due to enhanced EGF signaling (Goldshmit et al, 2004).…”
Section: Late Attenuation Of Rtk Signaling Via Receptor Ubiquitination and Degradationmentioning
confidence: 99%
“…Os trabalhos nestes locais requerem pessoas com formação individual e coletiva com vista a atenuar as ameaças ocupacionais e ambientais. O treinamento e preparação desta natureza é uma exigência básica militar e facilmente se traduz em operações de identificação em desastres de massa [15].…”
Section: Demystifying the Mysteries: Sexual Dimorphism In Primaryunclassified